Association of Sarcopenia With Toxicity and Survival in Postoperative Recurrent Esophageal Squamous Cell Carcinoma Patients Receiving Chemoradiotherapy - Xu, Ying-Ying; Zhou, Xi-Lei; Yu, Chang-Hua; Wang, Wan-Wei; Ji, Fu-Zhi; He, Dong-Cheng; Zhu, Wei-Guo; Tong, Yu-Suo (Frontiers in Oncology, 2021)
Background Sarcopenia has been associated with treatment-related toxicities and poor survival in cancer patients. Our aim was to investigate the prevalence of sarcopenia in postoperative recurrent esophageal squamous cell carcinoma (ESCC) patients receiving chemoradiotherapy (CRT) and evaluate associations with treatment-related toxicity and prognosis. Methods One hundred and eighty-four patients with postoperative locoregional recurrent ESCC receiving CRT between January 2014 and December 2016 were included. The skeletal muscle area (SMA) was measured at the third lumbar vertebra level. Sarcopenia was defined as skeletal muscle index (SMI = SMA/height2) less than 47.24/cm2/m2 for men and 36.92/cm2/m2 for women. Association of sarcopenia with overall survival (OS) was analyzed using univariate and multivariate cox regression models. Results Sarcopenia was observed in 94 of 184 (51.1%) patients. Sarcopenic patients had significantly higher rates of grade 3-4 toxicities compared to those without sarcopenia (36.2% vs 21.1%, p = 0.034). The survival rate at 12 and 24 months was 36.2% and 3.2% in the sarcopenic patients and 57.8% and 17.8% in the non-sarcopenic patients (p < 0.001). Multivariate cox regression analysis showed that sarcopenia was significantly associated with decreased OS (HR = 1.729, 95% CI 1.231-2.428, p = 0.002). Conclusions Sarcopenia is an independent indicator of poor survival in postoperative locoregional recurrent ESCC patients treated with CRT. Early nutritional interventions before treatment may improve the prognosis.